2021
DOI: 10.3389/fphy.2021.707113
|View full text |Cite
|
Sign up to set email alerts
|

GeO2 Doped Optical Fiber Plasmonic Sensor for Refractive Index Detection

Abstract: In this article, a D-shaped optical fiber refractive index (RI) sensor based on surface plasmon resonance effect is demonstrated. The gold film is placed at the flat portion of the optical fiber along with the sensing analytes of the different RIs to excite the plasmonic interactions. Sensing properties are investigated by using the finite element method. The maximum sensitivity of the proposed sensor is achieved as high as 20863.20 nm/RIU with the maximum resolution of 4.79 × 10−6 RIU and figure of merit of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Finally, figure of merit (FOM) factor of the designed sensor is obtained from the following equation [40]:…”
Section: Methods and Device Structurementioning
confidence: 99%
“…Finally, figure of merit (FOM) factor of the designed sensor is obtained from the following equation [40]:…”
Section: Methods and Device Structurementioning
confidence: 99%
“…While increasing the dopant concentration slightly reduces sensitivity, the sensor's adaptable design and extended detection range offer promising applications for diverse analyte detection in practical sensing environments. Gangwar et al [133] demonstrated in Figure 4(b) a Dshaped optical fiber SPR sensor where a gold film is positioned at the flat portion of the fiber and GeO 2 is doped into the silica core. Through FEM analysis, sensing properties are explored, achieving a maximum sensitivity of 20863.20 nm/RIU, resolution of 4.79×10 À 6 RIU, and figure of merit of 308.38 RIU À 1 for an RI of 1.43.…”
Section: Germaniummentioning
confidence: 99%
“…The fiber core, with an RI, denoted as n co , comprises GeO 2 doped silica, facilitating light propagation within the core. The cladding, on the other hand, is made of fused silica [133] (CreativeCommonsLicense4.0., with permission from Springer).…”
Section: Plasmonic Materialsmentioning
confidence: 99%
“…Microchannel plasmon biosensors Photonic crystal fiber D-shaped photonic crystal fiber (PCF) sensor for malaria diagnosis. [95] MXenes-based biosensors Fiber optic SPR sensor A spectral SPR-based fiber optic to diagnose colorectal cancer. [96] Au nanowire-based biosensors Optics Embedded micro-drilled dual-channel approach [97] Au Nanowire-based biosensors Optical Fiber Refractive Index Concave-shaped refractive index sensor (CSRIS) exploiting localized surface plasmon resonance (LSPR).…”
Section: Plasmonic Biosensors Surface Plasmon Resonance (Spr)mentioning
confidence: 99%